Juridical Review on the Support of Inheritance Rights in the Perspective of Compilation of Islamic Law - Andri, Muhammad; Fareha, Nur (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Innovations in land registration, such as electronic land rights and certificates, aim to enhance the quality of land services. In Indonesia, digital transformation has driven the government to reform land services, notably through Law No. 11 of 2020 on Job Creation. Article 147 stipulates that land rights, property rights to flats, management rights, and related documents may be in electronic form. This regulation is implemented through Ministerial Regulation No. 1 of 2021 on Electronic Certificates and Ministerial Regulation No. 3 of 2023 on Issuing Electronic Documents in Land Registration. This study examines the legal certainty of electronic land certificates as proof of ownership and the legal protection of electronic land ownership data. A normative juridical approach is employed, utilizing qualitative descriptive research based on primary and secondary legal materials collected through literature study. The data analysis method processes legal materials to address formulated legal issues qualitatively and descriptively. The findings indicate: (1) Electronic land certificates qualify as electronic evidence with the same legal standing as traditional paper documents. (2) Legal protection for electronic land ownership data includes: (a) Preventive legal protection, ensuring personal data security through obligations imposed on the Electronic System Operator—specifically, the Minister of Agrarian and Spatial Planning/National Land Agency (ASP/HNLA)—to safeguard public data confidentiality. (b) Repressive legal protection, allowing affected individuals to file lawsuits against the government in case of data breaches.